PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PJLP SATUAN PELAKSANA LINGKUNGAN HIDUP KECAMATAN KEBAYORAN LAMA - Anita Febriyanti; Anggada Bayu Seta (Journal of Research and Publication Innovation, 2025)
This study aims to determine the influence of the work environment and work motivation on the performance of PJLP in the Environmental Management Unit of Kebayoran Lama District, both partially and simultaneously. The method used is quantitative with a descriptive approach. The sampling technique employed is saturated sampling, where the entire population becomes the sample, resulting in 57 respondents in this study. The research results show that the significant value for the effect of X1 (work environment) on Y (employee performance) is 0.004<0.01, and the F-calculated value is 63.891>F-table 2.55. Additionally, the significant value of X2 (work motivation) on Y (employee performance) is 0.000<0.01. Therefore, it can be concluded that Ha3 is accepted, indicating that X1 and X2 have a simultaneous effect on Y.